The efficacy of preliminary clinical evaluation for emergency department chest radiographs with trauma presentations in pre- and post-training situations. Issue 4 (November 2022) - Stevens, B.J.; Thompson, J.D.
Abstract: Introduction: The chest X-ray (CXR) is the most frequently performed radiographic examination. This study evaluates radiographers' ability to localise traumatic CXR pathology and provide a preliminary clinical evaluation (PCE) for these cases. Methods: This observer study was performed in a district general hospital in the United Kingdom (UK). A 58-case image bank was used with 20 positive cases. Participants were awarded a maximum of three points, based on abnormality recognition and descriptive accuracy. Localisation data were recorded with ROCView. Training was delivered via short online recorded tutorials covering an introduction of a systematic search strategy for CXR, how to recognise the common abnormalities covered in the tests, how to structure a PCE and multiple practice cases to review at participants' own pace. Pre- and post-training data was recorded. Results: Nine participants completed the study. Overall, pooled sensitivity remained consistent (78.9%–78.8%) following training, specificity and accuracy showed improvement of 79.0%–89.9% and 78.9%–86.0% respectively. An increase in the number of correct localisations and PCE scores were also evident. Participants performed better at correctly identifying a pneumothorax compared to skeletal abnormalities. Conclusion: Improvements in performance were evident for most participants' abnormality localisations and PCE scores, following the training intervention. The study highlighted areas of CXR PCE that may require further training, such as detecting superimposed or subtle abnormalities. Implications for practice: This study provides additional support for the development of PCE systems in additional areas of imaging practice.